SELF-ASSEMBLY OF NANOWIRES: COMPUTER SIMULATION OF DNA MACROMOLECULES - P.V. Komarov; P.S. Kutilin; L.V. Zherenkova; N.Yu. Sdobnyakov; D.N. Sokolov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2011)
The Monte Carlo method is employed to study the conditions of self-assembly of nanowires in the matrix of DNA in aqueous solution by Monte Carlo method. The metal coating is formed as a result of electrostatic interaction of negatively charged groups of the matrix molecule and positively charged functionalized gold nanoparticles. The model parameters are estimated at which continuous metal coatings are formed via self-assembly.